Genome-wide identification of the WRKY gene family in blueberry (Vaccinium spp.) and expression analysis under abiotic stress - Lei, Lei; Dong, Kun; Liu, Siwen; Li, Yadong; Xu, Guohui; Sun, Haiyue (Frontiers in Plant Science, 2024)
The WRKY transcription factor (TF) family is one of the largest TF families in plants and is widely involved in responses to both biotic and abiotic stresses. To clarify the function of the WRKY family in blueberries, this study identified the WRKY genes within the blueberry genome and systematically analyzed gene characteristics, phylogenetic evolution, promoter cis-elements, expression patterns, and subcellular localization of the encoded products. 57 VcWRKY genes were identified, and all encoding products had a complete WRKY heptapeptide structure and zinc-finger motif. The VcWRKY genes were divided into three subgroups (I-III) by phylogenetic analysis. Group II was divided into five subgroups: IIa, IIb, IIc, IId, and IIe. 57 VcWRKY genes were distributed unevenly across 32 chromosomes. The amino acids ranged from 172 to 841, and molecular weights varied from 19.75 to 92.28 kD. Intra-group syntenic analysis identified 12 pairs of duplicate segments. Furthermore, 34 cis-element recognition sites were identified in the promoter regions of VcWRKY genes, primarily comprising phytohormone-responsive and light-responsive elements. Comparative syntenic maps were generated to investigate the evolutionary relationships of VcWRKY genes, revealing the closest homology to dicotyledonous WRKY gene families. VcWRKY genes were predominantly expressed in the fruit flesh and roots of blueberries. The expression patterns of six VcWRKY genes from different subgroups under salt stress, alkali stress, saline-alkali stress, and drought stress by using RT-qPCR. The responses of VcWRKY genes to stress treatments were more strongly in leaves than in roots. Notably, VcWRKY13 and VcWRKY25 exhibited significant upregulation under salt stress, alkali stress, and saline-alkali stress, and VcWRKY1 and VcWRKY13 showed notable induction under drought stress. Subcellular localization analysis confirmed that VcWRKY13 and VcWRKY25 function within the nucleus. These findings establish a foundation for further investigation into the functions and regulatory mechanisms of VcWRKY genes and provide guidance for selecting stress-tolerant genes in the development of blueberry cultivars.